Comparison of local minocycline hydrochloride delivery and antimicrobial photodynamic therapy as adjuncts to mechanical debridement for the treatment of peri‑implant mucositis: A randomized controlled trial - Abdulrahman M. AlMubarak (Photodiagnosis and Photodynamic Therapy)
Objective: The aim was to compare the efficacy of local minocycline hydrochloride delivery (LMHD) and antimicrobial photodynamic therapy (aPDT) as adjuncts to mechanical debridement (MD) for the treatment of peri‑implant mucositis (PM). Methods: Patients with PM were included. The following information was retrieved from patients’ digital dental records: (a) age, (b) gender, (c) duration of implants in function, (d) number of implants, (e) depth of implant placement, and (f) mode of prosthesis retention. Information related to daily toothbrushing and flossing of interproximal spaces and the most recent visit to an oral healthcare provider was also recorded. Participants were randomly divided into three groups as follows: (a) MD + LMHD; (b) MD + aPDT, and (c) MD alone. Peri-implant modified plaque index (mPI), modified gingival index (mGI) and probing depth (PD) were measured at baseline and at 45 days follow-up. Peri-implant crestal bone levels were measured at baseline. Group comparisons were done using One-way analysis of variance and Bonferroni post-hoc adjustment tests. The correlation between peri‑implant clinical parameters and age, gender, and duration of implants in function was assessed using linear regression analysis. Level of significance was set at P < 0.05. Results: Twenty-two and 22 patients underwent MD with adjunct LMDH and aPDT, respectively. Twenty-two participants underwent MD alone. There was no difference in the mean ages of all individuals. At baseline, there was no difference in mPI, mGI and PD in all groups. At follow-up, mPI (P < 0.05), mGI (P < 0.05) and PD (P < 0.05) were higher among patients who underwent MD alone than individuals who received LMHD or aPDT as adjuncts to MD. There was no difference in mPI, mGI, and PD among individuals who underwent LMHD and aPDT as adjuvants to MD. Conclusion: In the short term, MD with adjunct LMHD or aPDT is effective for managing PM.